1995
DOI: 10.1089/hwm.1995.12.243
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Catalyzed Oxidation of Multiple-Ringed Aromatics

Abstract: The role of manganese (Mn) oxides in catalyzing the abiotic oxidation of polynuclear aromatic compounds (PNAs) has been investigated by monitoring the oxidation of dihydrodiol and dione PNAs and corresponding reduction of Mn in an aqueous environment. 1,4-, 1,3-, and 2,3-naphthalenediol, 1,4-naphthoquinone, and l,4-dihydroxy-9,10-anthracenedione (Quinizarin) were oxidized in an oxic, aqueous environment, where each of these organic compounds is soluble in water, except Quinizarin. A mathematical model is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Following previous research [5,21,22], Whelan and Sims [15] have suggested that the reductive-dissolution/organic-oxidation process could move through a free-radical formation prior to polymerization. Stone and Morgan [23] have mechanistically described this reductivedissolution/oxidation process in four steps: 1) precursor-complex formation (i.e., reductant adsorption), 2) electron transfer, 3) release of oxidized organic product, and 4) release of reduced metal ion.…”
Section: Effects Of Ph On Reductive Dissolution Of Manganese Oxide Pamentioning
confidence: 79%
See 4 more Smart Citations
“…Following previous research [5,21,22], Whelan and Sims [15] have suggested that the reductive-dissolution/organic-oxidation process could move through a free-radical formation prior to polymerization. Stone and Morgan [23] have mechanistically described this reductivedissolution/oxidation process in four steps: 1) precursor-complex formation (i.e., reductant adsorption), 2) electron transfer, 3) release of oxidized organic product, and 4) release of reduced metal ion.…”
Section: Effects Of Ph On Reductive Dissolution Of Manganese Oxide Pamentioning
confidence: 79%
“…The results in Figures 4 and 6 assume that separate organic controls are indicative of the initial concentration in the reaction vessel. Because separate reaction vessels are employed for the organic analyses (i.e., separate samples, controls, and blanks without subsampling), this assumption may be violated when variability between the controls are too great [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations